E-WOM In Urban Community Support Ariculture: Impact Of Customer Experience, Knowledge, And Involvement - Hesty Nurul Utami; Resti Arini; Tomy Perdana; Sulistyodewi Nur Wiyono; Dini Turipanam Alamanda; Dinar Mariam Kurniati (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
The demand for organic vegetables is continuously increasing to support healthy lifestyles that more people follow. Digital technology has facilitated this product marketing to serve a larger market, including agri-food marketing using social media that explicitly targets online communities. The growing participation in Community-Supported Agriculture (CSA) as an agricultural product direct selling initiative in Indonesia highlights the necessity to examine how customer experience, knowledge, and involvement stimulate electronic word-of-mouth (E-WOM) as a powerful promotion tool that consists of peer opinions and experiences aiming to foster sustainable consumer engagement and market expansion. This study aims to determine the effect of customer experience, product knowledge, and customer involvement on E-WoM on organic vegetable customers at an urban CSA in Bandung City that sells organic vegetables. The research employed a quantitative method with the Structural Equation Model – Partial Least Square (SEM-PLS). We sampled 60 respondents of the urban CSA customers. The results show that customer experience, product knowledge, and customer involvement significantly influence E-WoM. The research provides theoretical implications for consumer perceptions, engagement, and decision-making in shaping E-WoM impact, including practical implications on marketing organic products in online communities that support urban agricultural practices related to enhancing consumer trust, attracting new members, and promoting the sustainability of urban community-supported agriculture initiatives.